(untitled) (Fiep Bulletin - online, 2015)
The precocity of alcohol abuse is a recurring problem, especially among university students. Alcoholis usually used as an alternative to stress, or as a stimulant for better socialization. Objective: This study aims to ascertain the level of risk in the consumption of alcohol and how the latter can affect or not the academic performance of the student. Materials and methods: A cross-sectional, descriptive and quantitative study was conducted on a sample of one hundred and fifty (n = 150) college students from the state of São Paulo. Students were randomly selected among courses in various fields to participate in a self-administered anonymous questionnaire based on the AUDIT (Alcohol Use Disorders Identification Test), under the supervision of the research team. The aim was to collect information about the academic performance of students from the start of the course and to identify those that have a harmful use of alcohol. Results: Through the survey, it was found that 79.33% of the participants had low-risk drinking, but 48% of respondents reported having academic difficulties, and / or to achieve the course activities. Our data suggest that even moderate or occasional drinkers may show higher rates of problems associated with drinking than heavy drinkers risk damaging themselves or dependents. Conclusion: Although the study was performed to evaluate the average alcohol consumption and academic performance of college, based on the information obtained, it is worth stressing the need for support from family and educational institutions, so that the young do not become prematurely dependent.